Leadership Strategies in Mobile English as a Second Language Training - Jalovcic, Djenana; McCloud-Bondoc, Linda; Ralston, Anthony (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This paper reviews a pilot mobile learning project for English as a Second Language implemented by a unimodal distance education institution to present an argument favouring the use of a distributed leadership approach for sustainability of the project. The authors’ position is grounded in the literature which suggests that distributed leadership in mobile and distance learning can provide a framework for sustainability of this project.